Complete chloroplast genome sequence and phylogenetic analysis of Clerodendrum japonicum (Thunb.) Sweet (Ajugoideae, Lamiaceae). Issue 8 (3rd August 2021) - Chen, Gang; Wang, Li-guo; Wang, Ying-hua
Abstract: Clerodendrum japonicum (Thunb.) Sweet belongs to the genus Clerodendrum in the family Lamiaceae. It is an important medicinal plant with great ornamental and economic value. We sequenced and analyzed the complete chloroplast genome of C. japonicum by Illumina sequencing in this study. The full length of the complete chloroplast genome is 152, 215 bp, containing a pair of inverted repeat regions of 25, 705 bp (IRa and IRb) separated by a large single-copy region (LSC) of 83, 491 bp and a small single-copy region (SSC) of 17, 314 bp. The C. japonicum chloroplast genome encodes 131 genes, comprising 85 protein-coding genes, 37 tRNA genes, 8 rRNA genes, and 1 pseudogene. This study will be useful for further study on population, phylogenetic, and molecular genetic studies of this medicinal plant.